2013
DOI: 10.3389/fendo.2013.00056
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PAC1 Receptors in Rat Cerebellar Granule Cells Stimulates Both Calcium Mobilization from Intracellular Stores and Calcium Influx through N-Type Calcium Channels

Abstract: High concentrations of pituitary adenylate cyclase-activating polypeptide (PACAP) and a high density of PACAP binding sites have been detected in the developing rat cerebellum. In particular, PACAP receptors are actively expressed in immature granule cells, where they activate both adenylyl cyclase and phospholipase C. The aim of the present study was to investigate the ability of PACAP to induce calcium mobilization in cerebellar granule neurons. Administration of PACAP-induced a transient, rapid, and monopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
(81 reference statements)
1
5
0
Order By: Relevance
“…Our results demonstrate that intracellular basal Ca 2+ was not increased by GDF-15 treatment; however, [Ca 2+ ] i in response to membrane depolarization and nifedipine-sensitive I Ca were up-regulated, suggesting the involvement of L-type Ca 2+ channels, although we cannot exclude the possibility that nifedipine-insensitive Ca 2+ channels or N-, P/Q- or R-type Ca 2+ channels were also modulated by GDF-15. A study of rat CGNs indicated that administration of PACAP (pituitary adenylate cyclase-activating polypeptide) induced a rapid rise in [Ca 2+ ] i and thereby stimulated Ca 2+ influx through N-type but not L-type Ca 2+ channels [ 31 ]. This difference may be explained by the fact that PACAP affects basal [Ca 2+ ] i , but not the response to membrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that intracellular basal Ca 2+ was not increased by GDF-15 treatment; however, [Ca 2+ ] i in response to membrane depolarization and nifedipine-sensitive I Ca were up-regulated, suggesting the involvement of L-type Ca 2+ channels, although we cannot exclude the possibility that nifedipine-insensitive Ca 2+ channels or N-, P/Q- or R-type Ca 2+ channels were also modulated by GDF-15. A study of rat CGNs indicated that administration of PACAP (pituitary adenylate cyclase-activating polypeptide) induced a rapid rise in [Ca 2+ ] i and thereby stimulated Ca 2+ influx through N-type but not L-type Ca 2+ channels [ 31 ]. This difference may be explained by the fact that PACAP affects basal [Ca 2+ ] i , but not the response to membrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…30C). These effects are in agreement with previous reports documenting PACAP-mediated increase in intracellular Ca 2+ levels [172,[199][200][201][202]. This result indicated that PACAP38 could enhance increased excitatory activity and Ca 2+ influx in neurons, which could be resulted from downregulation of Kv4.2 channels, as observed previously in chapter II.…”
Section: Pacap-mediated Dephosphorylation Of the Kv21 Channel Is Indsupporting
confidence: 93%
“…These kinases have been previously shown to phosphorylate glutamatergic NMDA and AMPA receptors leading to their enhanced activation [119][120][121][122]181]. In addition, PACAP can activate both L-type and N-type calcium channels which are abundantly expressed on neuronal dendrites and soma [199,214]. All these mechanisms in addition to Kv4.2 phosphorylation can result in increased dendritic and overall neuronal excitability leading to increases in electrical signal input to the soma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that PACAP promotes the increase of intracellular calcium from intracellular stores and calcium influx through calcium channels. 45,46 The mobilization of calcium allows the activation of CaMKIV, and then the increase of CREB activity. 47,48 More recently, it has been shown that PACAPmediated protective effect is also through the release of tissue plasminogen activator.…”
Section: Molecular Pathways Related To the Neuroprotection Of Cgnsmentioning
confidence: 99%